Enhancing and Building the Capacity of National Open University of Nigeria Staff in Open and Distance Learning Research - Tenebe, Vincent Ado; Ogidan, Rotimi (West African Journal of Open and Flexible Learning, 2013)
Most staff in the National Open University of Nigeria were employed with background knowledge of the conventional approach in conducting research only to realise later that knowledge of research in Open and Distance Learning (ODL) is needed because of its unique characteristics; part of which are learner support systems and effective use of technology to eliminate learner isolation. This has, therefore, necessitated the need to embark on building the capacity of staff in ODL research. The university channels resources into the project to ensure that staff acquire the relevant knowledge and skills in ODL research, particularly in areas that would improve practice and ensure competence in providing support services. This paper, therefore, discussed capacity building for staff of the National Open University of Nigeria in ODL research with a particular focus on the achievements, challenges and the way forward in the development of quality distance education in Nigeria.
Keywords: Capacity building; in-house training; train the trainers' workshop; ODL research